2019
DOI: 10.36232/jurnalpendidikanbahasa.v5i2.183
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Songs in Teaching Listening Skill at the Second Grade of SMP N 11 Kabupaten Sorong

Abstract: The use of song in the classroom can stimulate very positive associations to the study of a language. They can also make the classroom situation more enjoyable for students and increase the students’ interest to learn. Songs are chosen here because many of the students had listened to it. It can stimulate their motivation to learn, and to help the students learn English especially Listening Skill.The problem of this research can be stated how is using song effective in teaching listening skill at the second gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The findings showed that the score in the listening comprehension of students who are taught using English songs is higher than those who do not use songs. In the previous study by Kolin et al, (2019) there is a significant difference between learning outcomes using song media and learning without song media. In other words, the process of learning and listening to songs is an effective medium.…”
Section: T-testmentioning
confidence: 87%
“…The findings showed that the score in the listening comprehension of students who are taught using English songs is higher than those who do not use songs. In the previous study by Kolin et al, (2019) there is a significant difference between learning outcomes using song media and learning without song media. In other words, the process of learning and listening to songs is an effective medium.…”
Section: T-testmentioning
confidence: 87%
“…From songs, they also can learn many things, such as new words and cultures. For that reason, he believes that songs can be an attractive medium in language learning (Nurteteng et al, 2018). Fourth, to implement songs, the teacher should pay attention to several procedures for using English kids' songs as a learning media in teaching English.…”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental studies has also confirmed the various advantages of using songs to improve learners' langauge skills such as the improvement in listening Songs, Young Learners, Vocabulary Achievement skillls (Nurteteng, Sudibyo, Kolin, 2018;Chotimah & Astiyandha, 2020;Lestary & Seriadi, 2019;Listiyaningsih, 2017;Hidayat, 2013) and vocabularies achievement (Fachraini, 2017;Muthmainnah, 2017;Ma'rifat, 2017;Razmjoo, 2012). Furthermore, using songs in language classrooms can also increase students' motivation and enjoyment (Nadera, 2015;Israel, 2013;Millington, 2011).…”
Section: Spectralmentioning
confidence: 92%